Emerging Pharma Markets - Gupta, Shrey (2014)
This report is an individual extension of the group report done by our team for Parexel, covering a scenario planning exercise for the next 20 years’ time period as part of management project. One of the key highlights from the group report was the importance and opportunities in the emerging markets with respect to clinical trials. The purpose of this report is to investigate the opportunities and financial implications of growth in emerging markets for pharmaceutical contract research organizations, such as PARAXEL. This report will focus on both the strategic logics and financial effects of the growth opportunities in emerging markets. In developed markets, pharmaceutical companies experience a hostile environment to achieve sustainable growth rate due to expiring patents and high pricing pressures. This has led to an increase in the focus on developing and emerging markets as they are seen with a more optimistic outlook for medium to long-term prospects. Countries like Brazil, Russia, India and China, known as the BRIC countries, are some of the largest economies of the world and still offer growth prospects. Rapid growth can also be expected from some of the smaller economies in the Middle East, Latin America and Southeast Asia.